Negative and Near-Zero Thermal Expansion in A2M3O12 and Related Ceramic Families: A Review - Marinkovic, Bojan A.; Pontón, Patricia I.; Romao, Carl P.; Moreira, Thaís; White, Mary Anne (Frontiers in Materials, 2021)
This review presents the history of materials in the A2M3O12 and related ceramic families, including their unusual thermal expansion and the present understanding of its mechanism, and related factors such as hydroscopicity and the monoclinic to orthorhombic phase transition. Other properties, including thermomechanical, thermal and ionic conduction and optical properties, are presented in terms of present knowledge, challenges and opportunities for applications. One of the largest challenges is the production of monoliths, and various methods for consolidation and sintering are summarized. These ceramics have considerable promise when combined with other materials, and recent advances in such composites are presented. These matters are placed in the context of the potential applications of negative and near-zero thermal expansion ceramics, which still present challenges for future materials researchers.